ANALISIS PENINGKATAN SHARING KNOWLEDGE BEHAVIOR PADA PERUSAHAAN MELALUI MANAJEMEN PENGETAHUAN UNTUK PENINGKATAN KEMAMPUAN INOVASI INDIVIDU - Kadar Nurjaman (GoAcademica Research dan Publishing, 2021)
This study aims to analyze the increase in knowledge sharing behavior in companies through knowledge management to increase individual innovation abilities. This study uses a qualitative type of research with a case-study approach that focuses on individual units within the company. The study was conducted on two digital banks in Indonesia. The analysis was used to test the suitability between resources, the data analysis used the triangulation method and the data presentation was carried out using the descriptive method. Based on the results of research and analysis, it can be seen that bank company X and company bank Y have implemented KSB with formal and informal techniques. However, informal techniques have a direct positive impact on increasing the quality and innovation capacity of individuals, which in turn can make a positive contribution to the company's new services and products in accordance with market demands that are changing rapidly due to technological disruption.